2019
DOI: 10.1101/782896
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell time-series mapping of cell fate trajectories reveals an expanded developmental potential for human PSC-derived distal lung progenitors

Abstract: Alveolar epithelial type 2 cells (AEC2s) are the facultative progenitors responsible for maintaining lung alveoli throughout life, yet are difficult to access from patients for biomedical research or lung regeneration applications. Here we engineer AEC2s from human induced pluripotent stem cells (iPSCs) in vitro and use single cell RNA sequencing (scRNA-seq) to profile the detailed kinetics of their differentiation over time. We focus on both the desired target cells as well as those that appear to diverge to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Because the directed differentiation of human iPSCs in vitro is designed to recapitulate the sequence of developmental milestones that accompanies in vivo human fetal organogenesis, we first sought to understand the ontogeny of expression of the coronavirus receptor, ACE2, during human fetal development from early endodermal progenitors through increasingly more mature stages of alveolar development. By analyzing our previously published transcriptomic time series profiles of developing human fetal and adult primary AT2s (Hurley et al, 2020), we found that ACE2 expression increases from early to late canalicular stages of distal human lung development, and expression levels were similar to adult AT2 levels present by week 21 of gestation in developing alveolar epithelial cells (Figure 1E). We found the directed differentiation of human pluripotent stem cells (RUES2 embryonic stem cells and SPC2 iPSCs) in vitro into purified distal lung AT2-like cells resulted in cells expressing similar levels of ACE2 to those of adult primary cell controls in head-to-head comparisons (Figures 1E and S1,respectively).…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…Because the directed differentiation of human iPSCs in vitro is designed to recapitulate the sequence of developmental milestones that accompanies in vivo human fetal organogenesis, we first sought to understand the ontogeny of expression of the coronavirus receptor, ACE2, during human fetal development from early endodermal progenitors through increasingly more mature stages of alveolar development. By analyzing our previously published transcriptomic time series profiles of developing human fetal and adult primary AT2s (Hurley et al, 2020), we found that ACE2 expression increases from early to late canalicular stages of distal human lung development, and expression levels were similar to adult AT2 levels present by week 21 of gestation in developing alveolar epithelial cells (Figure 1E). We found the directed differentiation of human pluripotent stem cells (RUES2 embryonic stem cells and SPC2 iPSCs) in vitro into purified distal lung AT2-like cells resulted in cells expressing similar levels of ACE2 to those of adult primary cell controls in head-to-head comparisons (Figures 1E and S1,respectively).…”
Section: Resultsmentioning
confidence: 80%
“…iAT2s in ALI Culture Are Permissive to SARS-CoV-2 Infection and Replication In order to develop a human model system, we used the technique of directed differentiation (Jacob et al, 2017(Jacob et al, , 2019 to generate iAT2s from either human embryonic stem cells or iPSCs engineered to carry a tdTomato reporter targeted to the endogenous SFTPC locus (Hurley et al, 2020;Jacob et al, 2017). In 3D Matrigel cultures, we established self-renewing epithelial spheres composed of purified iAT2s, >90% of which expressed surfactant protein-C (SFTPC), the canonical AT2 marker, as monitored by flow cytometry assessment of the SFTPC tdTomato reporter at each passage in culture (Figures 1A and 1B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As expected NGFR was only expressed in the basal-like population cultured in BC medium (cluster 1; Figures 2F). Notably, we have previously demonstrated that plasticity of iPSC cells undergoing lung directed differentiation can sometimes result in reversion to non-lung endodermal lineages (McCauley et al 2018;Hurley et al 2019), however the day 30-32 sorting step for GFP+/TOM+ cells significantly reduced the percentage of non-lung endoderm cells in both conditions to less than 0.05% of all cells (Figure S3B).…”
Section: Ipsc-derived Airway Progenitors Adopt a Molecular Phenotype Similar To Primary Basal Cellsmentioning
confidence: 86%